Engineered Schwann Cell-Based Therapies for Injury Peripheral Nerve Reconstruction - Su, Qisong; Nasser, Moussa Ide; He, Jiaming; Deng, Gang; Ouyang, Qing; Zhuang, Donglin; Deng, Yuzhi; Hu, Haoyun; Liu, Nanbo; Li, Zhetao; Zhu, Ping; Li, Ge (Frontiers in Cellular Neuroscience, 2022)
Compared with the central nervous system, the adult peripheral nervous system possesses a remarkable regenerative capacity, which is due to the strong plasticity of Schwann cells (SCs) in peripheral nerves. After peripheral nervous injury, SCs de-differentiate and transform into repair phenotypes, and play a critical role in axonal regeneration, myelin formation, and clearance of axonal and myelin debris. In view of the limited self-repair capability of SCs for long segment defects of peripheral nerve defects, it is of great clinical value to supplement SCs in necrotic areas through gene modification or stem cell transplantation or to construct tissue-engineered nerve combined with bioactive scaffolds to repair such tissue defects. Based on the developmental lineage of SCs and the gene regulation network after peripheral nerve injury (PNI), this review summarizes the possibility of using SCs constructed by the latest gene modification technology to repair PNI. The therapeutic effects of tissue-engineered nerve constructed by materials combined with Schwann cells resembles autologous transplantation, which is the gold standard for PNI repair. Therefore, this review generalizes the research progress of biomaterials combined with Schwann cells for PNI repair. Based on the difficulty of donor sources, this review also discusses the potential of “unlimited” provision of pluripotent stem cells capable of directing differentiation or transforming existing somatic cells into induced SCs. The summary of these concepts and therapeutic strategies makes it possible for SCs to be used more effectively in the repair of PNI.